2018
DOI: 10.3390/ijms19072133
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Regulates Wnt/β-Catenin and NFκB Signaling Pathway through Dvl1

Abstract: Neuroglobin is an endogenous neuroprotective protein, but the underlying neuroprotective mechanisms remain to be elucidated. Our previous yeast two-hybrid screening study identified that Dishevelled-1, a key hub protein of Wnt/β-Catenin signaling, is an interaction partner of Neuroglobin. In this study, we further examined the role of Neuroglobin in regulating Dishevelled-1 and the downstream Wnt/β-Catenin and NFκB signaling pathway. We found that Neuroglobin directly interacts with Dishevelled-1 by co-immunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Overexpression of DVL is known to enhance the activation of Wnt signaling and may play a role in the progression of several cancers [27][28][29][30][31][32][33][34][35][36][37]. e proto-oncogene DVLl is an important component of the Wnt/β-catenin signaling pathway and is a key cytoplasmic regulator that prevents degradation of the β-catenin protein, and its high expression in tumors is associated with malignancy [38]. Previous studies have reported that both DVL1 and DVL3 proteins are overexpressed in NSCLC and are associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of DVL is known to enhance the activation of Wnt signaling and may play a role in the progression of several cancers [27][28][29][30][31][32][33][34][35][36][37]. e proto-oncogene DVLl is an important component of the Wnt/β-catenin signaling pathway and is a key cytoplasmic regulator that prevents degradation of the β-catenin protein, and its high expression in tumors is associated with malignancy [38]. Previous studies have reported that both DVL1 and DVL3 proteins are overexpressed in NSCLC and are associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 This effect seems to be related to the regulatory impact of Ngb on the Wnt/βcatenin and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathways, which induce the proteasomal degradation of Disheveled-1. 21 Although most of the details of the mechanisms through which Ngb exerts its neuroprotective activity are unknown, colocalization studies in cells of the nervous system suggest a direct interaction between Ngb and mitochondria. It has been suggested that Ngb could participate in regulating energy metabolism and apoptosis mechanisms through its interaction with ferric cytochrome c. This antiapoptotic function of ferric cytochrome c requires the participation of Ngb-reducing activity on ferric cytochrome C, which prevents the activation of caspase-9.…”
Section: Neuroglobin Functionsmentioning
confidence: 99%
“… 20 This effect seems to be related to the regulatory impact of Ngb on the Wnt/β-catenin and Nuclear Factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathways, which induce the proteasomal degradation of Disheveled-1. 21 …”
Section: Neuroglobinmentioning
confidence: 99%

The Role of Neuroglobin in the Sleep-Wake Cycle

García-García,
Acosta-Hernández,
Beltrán-Parrazal
et al. 2023
Sleep Sci
“…Furthermore, the specific effect of increasing the amount of Ngb in retinal cells has been demonstrated by the injection of exogenous Ngb after a transient hypoxia, which turned out to be effective in decreasing the levels of inflammatory chemokines (IL-6, TNFα, IL-1B, RANTES, MCP-1, and VEGF) and microglia activation [ 150 ]. This effect appears to be linked to the regulatory effect of Ngb on the Wnt/β-catenin and NF- k B signaling pathways, which is exerted mostly through the induction of the proteasomal degradation of Dishevelled-1, a key hub protein eliciting these two processes [ 151 ].…”
Section: Possible Patho-physiological Roles Of Neuroglobinmentioning
confidence: 99%